Clinical, Diagnostic, and Treatment Characteristics of SDHA-Related Metastatic Pheochromocytoma and Paraganglioma - Jha, Abhishek; de Luna, Kristine; Balili, Charlene Ann; Millo, Corina; Paraiso, Cecilia Angela; Ling, Alexander; Gonzales, Melissa K.; Viana, Bruna; Alrezk, Rami; Adams, Karen T.; Tena, Isabel; Chen, Alice; et al. (Frontiers in Oncology, 2019)
Background: Pheochromocytoma and paraganglioma (PHEO/PGL) are rare neuroendocrine tumors which may cause potentially life-threatening complications, with about a third of cases found to harbor specific gene mutations. Thus, early diagnosis, treatment, and meticulous monitoring are of utmost importance. Because of low incidence of succinate dehydrogenase complex subunit A (SDHA)-related metastatic PHEO/PGL, currently there exists insufficient clinical information, especially its diagnostic and treatment characteristics. Methods: Ten patients with SDHA-related metastatic PHEO/PGL were followed-up prospectively and/or retrospectively between January 2010 to July 2018. They underwent biochemical tests (n=10), 123I-MIBG (n=9) scintigraphy, and multiple whole-body positron emission tomography/computed tomography (PET/CT) scans with 68Ga-DOTATATE (n=10), 18F-FDG (n=10), and 18F-FDOPA (n=6) PET/CT. Results: Our findings suggest that these tumors can occur early and at extra-adrenal locations, behave aggressively, and have a tendency to develop metastatic disease within a short period of time. None of our patients had a family history of PHEO/PGL making them appear sporadic. Nine (n=9/10, 90%) patients showed abnormal PHEO/PGL-specific biochemical markers with predominantly noradrenergic and/or dopaminergic phenotype, suggesting their utility in diagnosing and monitoring the disease. Per patient detection rates of 68Ga-DOTATATE (n=10/10), 18F-FDG (n=10/10), 18F-FDOPA (n=5/6) PET/CT, and 123I-MIBG (n=7/9) scintigraphy were 100%, 100%, 83.33%, and 77.77%, respectively. Five of 7 (n=5/7; 71.43%) 123I-MIBG positive patients had minimal 123I-MIBG avidity or detected very few lesions compared to widespread metastatic disease on 18F-FDG PET/CT, implying that diagnosis and treatment with 123/131I-MIBG is not a good option. 68Ga-DOTATATE PET/CT was found to be superior or equal to 18F-FDG PET/CT in 7 (n=7/10, 70.0%) patients and hence is recommended for evaluation and follow-up of these patients. All 7 (n=7/7, 100%) patients who received conventional therapies (chemotherapy, somatostatin analog therapy, radiation therapy, 131I-MIBG, peptide receptor radionuclide therapy) in addition to surgery showed disease progression. Conclusion: In our cohort of patients, SDHA-related metastatic PHEO/PGL followed a disease-course similar to that of SDHB-related metastatic PHEO/PGL showing highly aggressive behavior, similar imaging and biochemical phenotypes, and suboptimal response to conventional therapies. Therefore, we recommend careful surveillance of the affected patients and a search for effective therapies.